2016
DOI: 10.1016/j.biochi.2016.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Structural features and activity of Brazzein and its mutants upon substitution of a surfaced exposed alanine

Abstract: Brazzein (Brz) is a member of sweet-tasting protein containing four disulfide bonds. It was reported as a compact and heat-resistant protein. Here, we have used site-directed mutagenesis and replaced a surface-exposed alanine with aspartic acid (A19D mutant), lysine (A19K mutant) and glycine (A19G mutant). Activity comparisons of wild-type (WT) and mutants using taste panel test procedure showed that A19G variant has the same activity as WT protein. However, introduction of a positive charge in A19K mutant led… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…Given the high thermal stability and low chemical stability of Brazzein reported in the previous studies, the presence of disulfide bonds profoundly influenced the structural integrity of the protein 5 . In summary, the antithetical properties of p.A19K mutants on the protein activity revealed that the presence of charged residue at this position may exert a profound effect on the interaction between protein and corresponding receptor.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Given the high thermal stability and low chemical stability of Brazzein reported in the previous studies, the presence of disulfide bonds profoundly influenced the structural integrity of the protein 5 . In summary, the antithetical properties of p.A19K mutants on the protein activity revealed that the presence of charged residue at this position may exert a profound effect on the interaction between protein and corresponding receptor.…”
Section: Resultsmentioning
confidence: 94%
“…Further, Brazzein protein is isolated from the fruit of Pentadiplandra brazzeana Baillon , composing of the three strands of antiparallel β-sheet, as well as a short α-helix connected by loops. It consists of 54 residues and has a molecular weight of about 6.5 kDa, in the structure of which eight Cys residues generate four disulfide bonds between the beta-sheets 5 , 6 . The protein is predicted to exhibit antibacterial and antifungal properties due to specific structural characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some models of receptor activation by brazzein have been proposed, the exact mechanism is not known. Interestingly, substitutions of some amino acid residues have been shown to significantly increase the sweetness of brazzein [7,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Since sweet-tasting proteins are useful as low-calorie sweeteners as well as a substitute for sucrose, a number of investigations have been performed to clarify why sweet-tasting proteins elicit a sweet taste, and how sweet-tasting proteins interact with sweet receptor (Kohmura et al, 1992 ; Kim and Weickmann, 1994 ; Slootstra et al, 1995 ; Somoza et al, 1995 ; Assadi-Porter et al, 2000 , 2010a , b ; Kaneko and Kitabatake, 2001 ; Temussi, 2002 , 2006 , 2011 ; Jin et al, 2003 ; Jiang et al, 2004 ; Tancredi et al, 2004 ; Masuda et al, 2005a , b , 2013 , 2016 ; Esposito et al, 2006 ; Walters and Hellekant, 2006 ; Koizumi et al, 2007 , 2015 ; Kurimoto et al, 2007 ; Li et al, 2008 ; Nakajima et al, 2008 , 2011 ; Ohta et al, 2008 , 2011a , b ; Ide et al, 2009 ; Walters et al, 2009 ; Xue et al, 2009 ; Dittli et al, 2011 ; Templeton et al, 2011 ; Liu et al, 2012 , 2016 ; Cornilescu et al, 2013 ; Lee et al, 2013 ; Rega et al, 2015 ; Ghanavatian et al, 2016 ; Leone et al, 2016 ; Lim et al, 2016 ; Singarapu et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%